Faktor Penentu Brand Trust Pada Oronamin C Melalui Brand Image - Astuti, Prida Ariani Ambar; Deanra, Tresia (Research and Community Service UNIVERSITAS KALBIS, 2024)
A brand is an essential element for a company in building trust and image. Therefore, many methods can be used, one of which is using brand ambassadors and increasing brand awareness. This research aims to identify and analyze the extent to which the influence of brand ambassadors Vincent and Desta, then brand awareness affects brand trust though the brand image of oronamin C. A positivist paradigm with a quantitative approach is used in this study, with an explanatory survey method conducted on Instagram followers of @oronaminc.id. The collected data was then processed using the SmartPLS 3.2.9 analysis tool with the Structural Equation Modelling (SEM)-PLS method. The results of this study show that brand ambassadors do not directly significantly influence brand trust. However, brand ambassadors significantly influence brand trust through the brand image formed on the Oronamin C product with value of 10.9%. Meanwhile, brand awareness has a direct significant impact on brand trust with value of 41,9% and significantly influences brand trust through the brand image with value of 25,1%